2010
DOI: 10.1007/s11940-010-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Coagulopathy in Intracranial Hemorrhage

Abstract: Intracranial hemorrhage (ICH) complicated by coagulopathy is a medical emergency, which can delay neurosurgical intervention, lead to larger hematoma size, and increase mortality until the coagulopathy is corrected. Prompt recognition of coagulopathy during ICH is essential for correct, rapid treatment to reduce ongoing bleeding and improve survival. The proper treatment of a coagulopathic ICH patient is centered on rapid identification of the coagulopathic defect and correction of the underlying coagulopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…OAT is associated with higher baseline ICH volume, increased risk of hematoma expansion and poor outcome 28 . Coagulopathy correction is aimed at preventing continued bleeding.…”
Section: Acute Managementmentioning
confidence: 99%
“…OAT is associated with higher baseline ICH volume, increased risk of hematoma expansion and poor outcome 28 . Coagulopathy correction is aimed at preventing continued bleeding.…”
Section: Acute Managementmentioning
confidence: 99%
“…However, because warfarin may only contribute to rather than cause a role in the pathogenesis of ICH [146], discontinuing warfarin therapy with the administration of vitamin K is not sufficient. PCC [5, 24], rFVIIa [5], or FFP [60] are often considered [3, 4, 107]. Schlunk et al [148] compared rFVIIa and PCC use in experimental warfarin-associated ICH and showed that they both could reduce the haematoma enlargement, with no significant difference in the reduction.…”
Section: Acute Progressing Haemorrhagic Strokementioning
confidence: 99%
“…For anticoagulants, such as dabigatran, rivaroxaban or lepirudin, the previous antithrombotic therapy could also be applied, although there is no consensus for the treatment protocol [3, 95]. Because the role of antiplatelets in ICH has not been established, there is no recommended therapy for reversal, whereas the application of desmopressin acetate was reported by several researchers [3].…”
Section: Acute Progressing Haemorrhagic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Coagulopathy can not only be induced by anticoagulant medication [4] or extensive treatment with intravenous fluids [2], but can also origin from hyper activation of coagulation with subsequent consumption of coagulation factors and platelets [5,6]. Coagulopathy is primarily diagnosed by measurements of prothrombin time (PT) or International Normalized Ratio (INR), activated partial thromboplastine time (APTT) and/or platelet count.…”
Section: Introductionmentioning
confidence: 99%